Comparison of Scalar Magnetic Field Data of China Seismo-Electromagnetic Satellite and Swarm Bravo Satellite - Jianing, Zhang; Bingjun, Cheng; Yuqi, Tong; Yuanqing, Miao; Bin, Zhou; Andreas, Pollinger; Xinghong, Zhu; Yanyan, Yang; Xiaochen, Gou; Yiteng, Zhang; Jindong, Wang; Lei, Li; et al. (Frontiers in Earth Science, 2022)
Based on the in-orbit magnetic field data of the China Seismo-Electromagnetic Satellite (CSES) and Swarm satellites, some research studies on the data consistency cross comparison were carried out. The condition applied is that two satellites pass by in a relatively short period of time and through the spatial location at a relatively close range, and different spatial-temporal scale standards were set, combined with the Kp index to screen for geomagnetic quiet periods. Then, with the help of the CHAOS model, indirect analysis was realized. Furthermore, the difference between the in-orbit data and model value was visualized, and the phenomenon and possible reason for data variation with time and geomagnetic latitude variation were analyzed. These analysis results are displayed in this study, which may evaluate the reliability of the satellite magnetic field detection data and the consistency of multiple satellite detection results and provide a methodological reference for carrying out similar evaluation and analysis subsequently.